CHOROIDAL NEVUS IMAGING FEATURES IN 3, 806 CASES AND RISK FACTORS FOR TRANSFORMATION INTO MELANOMA IN 2, 355 CASES: The 2020 Taylor R. Smith and Victor T. Curtin Lecture. Issue 10 (October 2019) - Shields, Carol L.; Dalvin, Lauren A.; Ancona-Lezama, David; Yu, Michael D.; Di Nicola, Maura; Williams, Basil K.; Lucio-Alvarez, J. Antonio; Ang, Su Mae; Maloney, Sean; Welch, R. Joel; Shields, Jerry A.
Abstract : Purpose: To use multimodal imaging for identification of risk factors for choroidal nevus transformation into melanoma. Methods: Retrospective chart review of 3806 consecutive choroidal nevi with imaging and 2355 choroidal nevi with additional follow up to identify factors predictive of transformation of choroidal nevus into melanoma. Results: The median patient age was 62.5 years and Caucasian race in 3167 (95%). The choroidal nevus demonstrated median basal diameter of 4.0 mm and thickness of 1.4 mm. Imaging included optical coherence tomography (OCT) showing subretinal fluid (SRF) in 312 (9%), ultrasonography (US) with acoustic hollowness in 309 (9%), and hyper-autofluorescence (AF) in 100 (3%). Of those 2355 choroidal nevi with follow up, Kaplan-Meier estimates of nevus transformation into melanoma at 1, 5, and 10 years were 1.2%, 5.8%, and 13.9%, respectively. Multivariate analysis, using multimodal imaging for detection of factors predictive of nevus transformation into melanoma, included thickness >2 mm on US (hazard ratio (HR) 3.80, p < 0.0001), SRF on OCT as cap over nevus (HR 3.00, p < 0.0001) or SRF ⩽3 mm from nevus margin (HR 3.56, p = 0.0003), symptomatic vision loss ⩽20/50 on Snellen visual acuity (VA) (HR 2.28, p = 0.005), orange pigment (lipofuscin) hyperautofluorescence on AF (HR 3.07, p = 0.0004), acoustic hollowness on US (HR 2.10, p = 0.0020), and tumor diameter >5 mm on photography (HR 1.84, p = 0.0275). These factors can be recalled by the mnemonic "To Find Small Ocular Melanoma Doing IMaging" (TFSOM-DIM) representing Thickness >2 mm (US), Fluid subretinal (OCT), Symptoms vision loss (VA), Orange pigment (AF), Melanoma hollow (US), and DIaMeter >5mm (photography). The mean 5-year estimates of nevus growth into melanoma were 1% (HR 0.8) for those with 0 risk factor, 11% (HR 3.09) with 1 factor, 22% (HR 10.6) with 2 factors, 34% (HR 15.1) with 3 factors, 51% (HR 15.2) with 4 factors, 55% (HR 26.4) with 5 risk factors, and not-estimable with all 6 risk factors. Conclusion: In this analysis, multimodal imaging was capable of detecting risk factors for nevus transformation into melanoma, including thickness >2 mm (US), fluid subretinal (OCT), symptoms vision loss (Snellen acuity), orange pigment (AF), melanoma hollowness (US), and diameter >5 mm (photography). Increasing number of risk factors imparts greater risk for nevus transformation into melanoma, including thickness >2 mm (US), fluid subretinal (OCT), symptoms vision loss (Snellen acuity), orange pigment (AF), melanoma hollowness (US), and diameter >5 mm (photography). Increasing number of risk factors imparts greater risk for transformation. Abstract : Multimodal imaging identified significant risk factors for choroidal nevus transformation into melanoma, including thickness >2 mm (ultrasonography, hazard ratio [HR] 3.80), fluid subretinal (optical coherence tomography, HR 3.56), symptoms vision loss (Snellen acuity, HR 2.28), orange pigment (autofluorescence, HR 3.07), melanoma hollowness (ultrasonography, HR 2.1), and diameter >5 mm (photography, HR 1.84).